Disequilibrium-induced initial Os isotopic heterogeneity in gram aliquots of single basaltic rock powders: Implications for dating and source tracing - Li, J.; Wang, Xuan-Ce; Xu, J.; Xu, Y.; Tang, G.; Wang, Q. (Elsevier, 2015)
The Re–Os isotopic heterogeneity of mantle-derived rocks has been well documented. However, it is unclear whether and how the Os isotopic heterogeneity of a mantle source can influence Re–Os isotopic dating and source tracing of mantle-derived melts. Here we report that replicate analyses of gram aliquots of single basaltic powders (one of reference material BHVO-2 and three of the Hatu basalts from the western Junggar region, China) show large variations in both Os concentrations and isotopic ratios. More importantly, these replicate data define good apparent Re–Os isochron correlations, yielding ages significantly older than their formation ages, and display remarkable correlations between the 187Os/188Os ratio and the reciprocal of the common Os concentration (i.e., 1/192Os). This indicates that the initial Os isotopic composition in a basaltic magmatic system may be heterogeneous and cannot be homogenized by pulverizing. Theoretical and mathematical deduction demonstrates that the observed apparent Re–Os isochron correlations are the result of binary mixing without complete isotopic equilibrium at the time of formation, primarily due to limited diffusional exchange of Os isotopes between refractory Os-bearing inclusions and host minerals under mantle conditions. The regressed initial Os isotopic composition may bias the true value of the mantle source. Pulsed mantle melting and magma mixing during ascent are potential processes responsible for such initial Os isotopic heterogeneity in basaltic rock systems. Thus, when using the Re–Os isotopic system to date and to trace the source of basaltic rocks or other rocks with relatively low Os concentrations, it is necessary to consider whether the initial Os isotopic composition was heterogeneous or whether it had reached complete isotopic equilibrium.